2018
DOI: 10.47672/ajlg.325
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intellectual Stimulation on Employee Performance in Regulatory State Corporations in Kenya

Abstract: Purpose: The purpose of the study was to determine the effect of intellectual stimulation on employee performance in regulatory state corporations in KenyaMethodology: Descriptive correlation design was employed. Proportionаtе strаtifiеd rаndom sаmpling mеthod wаs usеd to sеlеct 130 senior level managers from the target population. Primary data was collected using a closed ended questionnaire. Pearson’s correlation and   regression techniques were used to analyse the data.Findings: The study revealed a positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Kinya and Eliud (2021) found that top managers pushed subordinate staff to achieve more by articulating high expectations that subordinate staff aspired to fulfil and encouraging optimism. To increase employee performance in regulatory state firms, leaders should be committed to the organization's mission by speaking optimistically about future goals and collaborating with employees to move people forward with inspiring words and actions (Anyiko-Awori et al, 2018). Besides that, according to Hasija et al (2019), a leader who emanates inspirational motivation can have a big impact on how their employees participate in instituterelated activities and contribute to the institution's growth and survival.…”
Section: Inspirational Motivationmentioning
confidence: 99%
“…Kinya and Eliud (2021) found that top managers pushed subordinate staff to achieve more by articulating high expectations that subordinate staff aspired to fulfil and encouraging optimism. To increase employee performance in regulatory state firms, leaders should be committed to the organization's mission by speaking optimistically about future goals and collaborating with employees to move people forward with inspiring words and actions (Anyiko-Awori et al, 2018). Besides that, according to Hasija et al (2019), a leader who emanates inspirational motivation can have a big impact on how their employees participate in instituterelated activities and contribute to the institution's growth and survival.…”
Section: Inspirational Motivationmentioning
confidence: 99%